The help : a novel - 277650 Stockett, Kathryn (New York : Berkley Books, 2011)
Limited and persecuted by racial divides in 1962 Jackson, Mississippi, three women, including an African-American maid, her sassy and chronically unemployed friend, and a recently graduated white woman, team up for a clandestine project.